An Enhancement Method for Japanese-English Automated Translation - Wloka, Bartholomäus; Winiwarter, Werner (Investigationes Linguisticae, 2010)
We present a method for improving existing statistical machine translation methods using a knowledge base compiled from a bilingual corpus as well as sequence alignment and pattern matching techniques from the area of machine learning and bioinformatics. An alignment algorithm identifies similar sentences, which are then used to construct a better word order for the translation. Our preliminary test results indicate a significant improvement of the translation quality.